Effect of Earthing-Up Frequency on Growth and Yield of Anchote (Coccinia abyssinica) Varieties at Gimbi District, Western Ethiopia - Habte Wakjira; Weyessa Garedew; Amsalu Nebiyu; Garome Shifaraw (International Journal of Agronomy)
Anchote (Coccinia abyssinica (Lam.) Cogn) is a tuberous root crop native to Ethiopia. It is a good source of protein, carbohydrates, calcium, and iron. However, little attention has been given to the improvement of genetic and agronomic practices such as selection of variety, staking, weeding, fertilizer application, and earthing-up frequency. Thus, the attainable yield is below the potential. The experiment was arranged in a 3 × 5 factorial arranged in a randomized complete block design (RCBD) with three replications with the objective of determining the effect of earthing-up frequency on the growth and yield of anchote varieties. The interaction effect of earthing-up frequencies and varieties significantly affected anchote leaf number plant−1, shoot dry weight plant−1, unmarketable tuber weight ha−1, vine diameter, shoot fresh weight plant−1, tuber fresh weight plant−1, marketable tuber weight ha−1, and total tuber yield ha−1. Total tuber yield ha−1 was perfectly correlated with tuber fresh weight plant−1 (r = 1), and all parameters were significantly correlated with tuber dry matter plant−1, and tuber dry matter plant−1 was positively and significantly correlated with total tuber yield ha−1 (r = 0.46). Consequently, the highest total tuber yield was observed from earthing-up four times (26.94 t ha−1) and three times (26.88 t ha−1) with Desta 01, while the lowest was observed from the control with Acc405 (15.11). The highest economical tuber yield was obtained from three times earthing-up frequency (26.878 t ha−1, 25.50 t ha−1, and 23.92 t ha−1 for Desta 01, Acc405, and Acc173), and the lowest was observed from the control (22.83 t ha−1, 15.11 t ha−1, and 21.11 t ha−1 for Desta 01, Acc405, and Acc173), respectively. Therefore, for the study area, it is better to apply three times earthing-up frequencies (35 days, 49 days, and 63 days from planting date for once, twice, and three times earthing-up, respectively) with Desta 01 variety followed by Acc405. Since the experiment was conducted using irrigation, it is suggested to be repeated under rainfed conditions to draw a definite conclusion.